Perancangan Konsep Color of Jungle pada Kids Center di Malang - Poppy F.N, Sineala Winnio Sumartono (Intra, 2013)
In this era globalization, parents treat an occupation as the main priority of all because an increase in daily necessities. As a result, parents are lack of caring to their children. Therefore, an alternative is needed to replace parentâs role at home. One of the alternative is using a nanny as motherâs helper to take care of their children. However, in fact, many of unexpected things happen, children are kidnapped and abandoned by their nanny. Eventually, many of parents take a decision to enter their children to school under the standard age. Moreover, a high technology development causes children lack of exercise because they prefer to play games rather than to exercise. Another effect of technology is a lack of social life. Hence, they become more individualism.Methodology planning is started from collecting data which includes direct survey, literature data, and typology. The next observations can be an interview, a study research at the same object and last but not least is methodology analysis, which is started from planning program until final design. The interior design ofÂ  kids center in Malang is using the concept of jungle, which helps children to interact directly to animals, plants and their friendsThe application concept of kids centerÂ  can be shown in each room. The room for 3 to 6 months old is using bird theme, 7 months old to 1 years oldâs room using squirell theme, the room for 2 to 3 years old is using fish theme, and then the room for 4Â  to 5 years room is using giraffe theme. The playing area for 2 to 5 years old is using the garden theme, for the dining room is designed by using mushroom theme, and the playground area is using monkey theme. In order to enlarge the space for children, the room is designed to have less furniture. Rooms are also designed to have a big ventilation so lights and natural air cycle or wind are maximized. Vinyl, carpet, multipleks with water based finishing or HPL are the materials. All appliances that applied are useful for brain storming for the childrenâs creativity and knowledge.